Application of Thermography to Detect Areas of Water Infiltration in the Dam Concrete Foundation - Miahkyi, O.; Meshkov, S.; Orel, R.; Storozhenko, V. (My University, 2024)
This paper introduces a methodology devised for thermographic inspection of concrete technical condition inside concrete dams. Water infiltration into a dam accelerates the processes of concrete degradation, so temperature fields provide important information about the dynamics of these processes. As a result of the thermal imaging survey of the observation gallery at a historic hydraulic structure, a formalized pattern of the temperature field inside the dam was acquired and the locations of temperature anomalies associated with infiltration were identified. At the leakage points, the water temperature differed from the concrete temperature by 1.0–2.9 °C, indicating different rates of water flow through the water wall and the gallery ceiling. The temperature of the gallery areas with increased infiltration was 1–2 °C higher than the 12.7 °C selected as the reference temperature. When recording the temperature fields, the optical axis of the thermal imager was directed along the gallery, and not perpendicular to the surfaces under study, as in construction thermography. To this end, a methodological approach was devised to eliminate distortions of the resulting thermograms caused by the curvature of the gallery and other factors. To remove images of extraneous thermal radiation sources from the thermograms and accurately identify the area under study, a method of shielding a part of the image using special masks was used. The comparative thermography method made it possible to eliminate difficulties in determining the emissivity of the gallery concrete surface. The proposed method of comparative thermography made it possible to compare the intensity of filtration processes in the dam body and to link the current state of the hydraulic structure with the history of its restoration. In general, the thermographic method makes it possible to supplement existing primary natural control with a formalized pattern of temperature field inside the dam.
Keywords: thermography; concrete dam; water infiltration; thermogram processing; infiltration criterion; inspection gallery